Value creation for emerging acquirers in other emerging economies : a comparison with developed market firms - Lobato, Maria Teresa Fernandes Guimarães (2012)
Over the past few years, emerging markets have been reinforcing their presence in the worldwide M&A activity. In fact, emerging acquirers are now targeting companies in order to tap into their fast economic growth and increasingly wealthy populations. As a consequence, we have to ask: Do cross-border acquisitions in emerging markets create positive and significant returns to their emerging acquirers? Are these higher than those of developed countries? We perform an event study on 657 deals involving emerging acquirers between 2002 and 2011 and compare with 1936 deals performed by developed country firms both in emerging markets. We find that emerging acquirers earn significantly higher returns than developed markets especially in the case of acquisition of control. Lastly, emerging companies of smaller size, who finance their transactions with cash and acquire control of the target, are more likely to incur higher value creation.